Metal composite compound powder, method for producing metal composite compound powder, and method for producing positive electrode active material for lithium secondary battery
The manufacturing method for metal composite compound powder, involving controlled heating and drying of metal hydroxide cakes, addresses the need for improved particle structure in lithium secondary batteries, resulting in enhanced initial efficiency and discharge capacity.
Patent Information
- Application Number
- JP2024108259
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-07-11
- Filing Date
- 2024-07-04
- Publication Date
- 2025-01-24
AI Technical Summary
Existing methods for producing positive electrode active materials for lithium secondary batteries do not adequately address the need for improved initial efficiency and particle structure to enhance battery performance.
A manufacturing method for metal composite compound powder involves heating a wet cake containing metal composite hydroxide with controlled water content, followed by surface shaving and drying to achieve specific particle distributions, resulting in a powder with optimized primary and secondary particle sizes and reduced moisture content.
The method produces a metal compound powder that enhances the initial efficiency of lithium secondary batteries by improving the particle structure, leading to higher discharge capacity and efficiency.
Smart Images

Figure 2025013235000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a metal composite compound powder, a method for producing the metal composite compound powder, and a method for producing a positive electrode active material for a lithium secondary battery. [Background technology]
[0002] For the purpose of improving the performance of positive electrode active materials for lithium secondary batteries, attempts have been made to control various aspects of the manufacturing process for positive electrode active materials for lithium secondary batteries.
[0003] For example, Patent Document 1 describes a method for producing a positive electrode active material for a lithium secondary battery, which includes a step of adjusting the particle size distribution of a metal composite compound by pulverizing a hydroxide raw material powder corresponding to the metal composite compound. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] WO2014 / 061580A1 Summary of the Invention [Problem to be solved by the invention]
[0005] From the viewpoint of improving the initial efficiency of lithium secondary batteries, there is room for further improvement in the physical properties of metal composite compounds, which are raw materials for positive electrode active materials for lithium secondary batteries.
[0006] The present invention has been made in view of the above circumstances, and has an object to provide a metal composite compound powder capable of obtaining a lithium secondary battery with high initial efficiency, a method for producing the same, and a method for producing a positive electrode active material for a lithium secondary battery. [Means for solving the problem]
[0007] The present invention has the following aspects. [1] A method for producing a metal composite compound powder, comprising: a step X of heating a wet cake containing a metal composite hydroxide containing at least Ni and moisture while flowing it in a heating device, and scraping a surface of the metal composite hydroxide contained in the wet cake, wherein a ratio of the moisture contained in the wet cake immediately before the step X is 5 mass % or more and 25 mass % or less with respect to a total mass of the wet cake, and a ratio of the moisture contained in the wet cake immediately before the step X with respect to a residence time of the wet cake in the heating device is 11 mass % / hour or less. [2] The method for producing a metal composite compound powder according to [1], wherein the maximum holding temperature in the step X is 100°C or higher and 300°C or lower. [3] The method for producing a metal composite compound powder according to [1] or [2], wherein the residence time is 0.2 to 8 hours. [4] The method for producing a metal composite compound powder according to any one of [1] to [3], wherein a proportion of moisture contained in the powder containing the metal composite hydroxide immediately after the step X is 1 mass % or less with respect to a total mass of the powder containing the metal composite hydroxide. [5] The method for producing a metal composite compound powder according to any one of [1] to [4], further comprising, prior to the step X, a step of neutralizing a solution containing at least a nickel salt solution under conditions of pH 10 to 13 and 20° C. to 80° C. [6] The method for producing a metal composite compound powder according to any one of [1] to [5], further comprising, prior to the step X, a step of removing moisture from the wet cake such that a proportion of moisture contained in the wet cake is 5 mass % or more and 25 mass % or less with respect to a total mass of the wet cake. [7] The method for producing a metal composite compound powder according to any one of [1] to [6], wherein the metal composite hydroxide further contains an element M, and the element M is one or more elements selected from the group consisting of Co, Mn, Al, Fe, Cu, Ti, Mg, W, Mo, Nb, Zn, Sn, Zr, Ga, V, B, Si, S and P. [8] A metal composite compound powder including secondary particles which are aggregates of a plurality of first primary particles and a plurality of second primary particles, and which contains at least Ni, wherein, when a dimension from an outermost surface of the secondary particle to a center of gravity in a cross section of the secondary particle is taken as 100%, the first primary particles are located in an area less than 10% from the outermost surface of the secondary particle, and the second primary particles are located in an area not exceeding 90% from the center of gravity, and a ratio of an average particle diameter of the second primary particles to an average particle diameter of the first primary particles is 1.5 or more. [9] The metal composite compound powder according to [8], wherein the average particle size of the first primary particles is 0.1 μm or more and 1.0 μm or less.
[10] The metal composite compound powder according to [8] or [9], wherein the average particle size of the secondary particles is 5 μm or more and 20 μm or less.
[11] The metal composite compound powder according to any one of [8] to
[10] , wherein the proportion of moisture contained in the metal composite compound powder is 1 mass % or less based on the total mass of the metal composite compound powder.
[12] The metal composite compound powder according to any one of [8] to
[11] , further containing an element M, wherein the element M is one or more elements selected from the group consisting of Co, Mn, Al, Fe, Cu, Ti, Mg, W, Mo, Nb, Zn, Sn, Zr, Ga, V, B, Si, S and P.
[13] A method for producing a positive electrode active material for a lithium secondary battery, comprising firing a mixture of the metal composite compound powder according to any one of [8] to
[12] and a lithium compound. Effect of the Invention
[0008] According to the present invention, it is possible to provide a metal composite compound powder capable of producing a lithium secondary battery with high initial efficiency, a method for producing the same, and a method for producing a positive electrode active material for a lithium secondary battery. [Brief description of the drawings]
[0009] [Figure 1] FIG. 2 is a schematic cross-sectional view of a secondary particle of a metal composite compound powder according to one aspect of the present embodiment. [Diagram 2] 1 is a scanning electron microscope image of a metal composite compound powder according to one embodiment of the present invention. [Diagram 3] 1 is a scanning electron microscope image of a metal composite compound powder in which the ratio of the average particle size of second primary particles to the average particle size of first primary particles is less than 1.5. [Figure 4] FIG. 1 is a schematic diagram illustrating an example of a lithium secondary battery. [Diagram 5] FIG. 1 is a schematic diagram illustrating an example of an all-solid-state lithium secondary battery. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] Hereinafter, a metal composite compound powder according to one aspect of the present invention will be described. In the following embodiments, preferred examples and conditions may be shared. In addition, in this specification, each term is defined as follows.
[0011] In this specification, metal composite compound powder is hereinafter referred to as "MCC", and cathode active material for lithium secondary batteries is hereinafter referred to as "CAM".
[0012] "Ni" refers to nickel atoms, not nickel metal. Similarly, "Co" and "Al" refer to cobalt atoms and aluminum atoms, etc., respectively.
[0013] For example, when a numerical range is described as "1-10 μm" or "1 to 10 μm," it means a range from 1 μm to 10 μm, including the lower limit of 1 μm and the upper limit of 10 μm.
[0014] The "cumulative volumetric particle size" is a value measured by a laser diffraction scattering method. Specifically, 0.1 g of MCC is added to 50 ml of a 0.2 mass % aqueous solution of sodium hexametaphosphate to obtain a dispersion in which the MCC is dispersed. Next, the particle size distribution of the obtained dispersion is measured using a laser diffraction scattering particle size distribution measuring device (e.g., Mastersizer 2000, manufactured by Malvern Instruments) to obtain a volume-based cumulative particle size distribution curve. In the obtained cumulative particle size distribution curve, the particle size value at 50% accumulation from the fine particle side is called the 50% cumulative volumetric particle size (hereinafter, D 50 and is the average particle size (μm) of the secondary particles in this specification.
[0015] The "composition analysis of MCC" is performed by the following method. For example, MCC is dissolved in hydrochloric acid, and then measured using an ICP optical emission spectrometer. As the ICP optical emission spectrometer, for example, Optima 7300 manufactured by PerkinElmer Co., Ltd. can be used. The composition of the metal composite hydroxide can also be measured in the same manner.
[0016] In this specification, the "method of producing a positive electrode for a lithium secondary battery" is as follows. CAM, a conductive material (acetylene black), and a binder (PVdF) are added and kneaded so that the composition is CAM:conductive material:binder = 92:5:3 (mass ratio), to prepare a paste-like positive electrode mixture. When preparing the positive electrode mixture, N-methyl-2-pyrrolidone is used as an organic solvent.
[0017] The obtained positive electrode mixture is applied to a 40 μm thick Al foil as a current collector and vacuum dried at 150 °C for 8 hours to obtain a positive electrode for a lithium secondary battery. The electrode area of this positive electrode for a lithium secondary battery is 1.65 cm 2 Let us assume that.
[0018] In this specification, the "method for manufacturing a lithium secondary battery" is as follows. The following operations are performed inside a glove box under an argon atmosphere. Place the positive electrode for a lithium secondary battery produced in "Manufacture of the Positive Electrode for a Lithium Secondary Battery" with the aluminum foil side facing down on the lower lid of the parts for a coin-type battery R2032 (manufactured by Hokuen Co., Ltd.), and place a laminated film separator (a laminate with a thickness of 16 μm obtained by laminating a heat-resistant porous layer on a porous polyethylene film) on top of it. Inject 300 μl of an electrolytic solution here. The electrolytic solution is a solution obtained by dissolving LiPF 6 in a mixed solution of ethylene carbonate, dimethyl carbonate, and ethyl methyl carbonate at a volume ratio of 30:35:35 so that the concentration becomes 1 mol / l.
[0019] Next, using metallic lithium as the negative electrode, place the negative electrode on the upper side of the laminated film separator, cover it with the upper lid through a gasket, and crimp it with a crimper to manufacture a lithium secondary battery (coin-type half cell R2032).
[0020] The "initial efficiency" means a value measured by performing charge and discharge of a lithium secondary battery under the following conditions.
[0021] (Charge and Discharge Test) Test temperature: 25°C Maximum charge voltage: 4.3 V, charge current: 0.2 CA, constant current and constant voltage charging Minimum discharge voltage: 2.5 V, discharge current: 0.2 CA, constant current discharge (Initial Efficiency) Initial efficiency (%) = Initial discharge capacity (mAh / g) / Initial charge capacity (mAh / g) × 100
[0022] <Manufacture of MCC> In one aspect of the present invention, a method for manufacturing an MCC includes heating a wet cake containing a metal composite hydroxide containing at least Ni and moisture while flowing it in a heating device, and scraping the surface of the metal composite hydroxide contained in the wet cake (hereinafter sometimes referred to as step X). The ratio of the moisture contained in the wet cake immediately before step X is 5-25% by mass based on the total mass of the wet cake, and the ratio of the moisture contained in the wet cake immediately before step X to the residence time of the wet cake in the heating device is 11% by mass / hour or less. Immediately before step X means within 30 minutes before performing step X, and immediately after step X means within 30 minutes after completion of the implementation of step X. The powder containing the metal composite hydroxide immediately after step X may hereinafter sometimes be referred to as powder X.
[0023] The metal composite hydroxide preferably contains at least Ni and preferably contains Ni and element M. Element M is one or more elements selected from the group consisting of Co, Mn, Al, Fe, Cu, Ti, Mg, W, Mo, Nb, Zn, Sn, Zr, Ga, V, B, Si, S, and P. From the viewpoint of improving the initial efficiency, as element M, one or more elements selected from the group consisting of Co, Mn, Al, Ti, Mg, W, Nb, Zr, and B are preferable.
[0024] The metal composite hydroxide preferably contains Ni and element M in the molar ratio represented by the following formula (A), and preferably is represented by the following formula (A'). Ni:M=(1-x):x (A) Ni (1-x) M x (OH) 2 (A’) (In formula (A) and formula (A'), M is the above element M, and the following formula (A) and the following formula (A') satisfy 0 < x ≦ 0.5.)
[0025] From the viewpoint of obtaining a lithium secondary battery with a large battery capacity, x in the above formula (A) and the above formula (A') is preferably more than 0 and 0.50 or less, more preferably more than 0 and 0.40 or less, still more preferably more than 0 and 0.30 or less, and particularly preferably more than 0 and 0.25 or less.
[0026] The metal composite hydroxide preferably contains Ni and element M1 in the molar ratio represented by the following formula (B), and more preferably is represented by the following formula (B’). Ni:M1:M2=(1-y-z):y:z (B) Ni (1-y-z) M1 y M2 z (OH) 2 (B’) (In formula (B) and formula (B’), M1 is one or more elements selected from the group consisting of Co, Mn, and Al, M2 is one or more elements selected from the group consisting of Fe, Cu, Ti, Mg, W, Mo, Nb, Zn, Sn, Zr, Ga, V, B, Si, S, and P, and formula (B) and formula (B’) satisfy 0 < y ≦ 0.5, 0 ≦ z ≦ 0.1, and 0 < y + z ≦ 0.5.)
[0027] From the viewpoint of obtaining a lithium secondary battery with a large battery capacity, the lower limit value of y is preferably 0.01. The upper limit value of y is preferably 0.30 or less, more preferably 0.20 or less, and still more preferably 0.15 or less. The upper limit value and the lower limit value of y can be arbitrarily combined. y is preferably 0.01 - 0.30, more preferably 0.01 - 0.20, and still more preferably 0.01 - 0.15.
[0028] When the metal composite hydroxide contains the above M2, from the viewpoint of obtaining a lithium secondary battery with good cycle characteristics, the lower limit value of z exceeds 0 and is preferably 0.01. From the viewpoint of obtaining a lithium secondary battery with a large battery capacity, the upper limit value of z is preferably 0.10, and more preferably 0.08. The upper limit value and the lower limit value of z can be arbitrarily combined. z is preferably 0 - 0.10, more preferably more than 0 and 0.10 or less, and still more preferably 0.01 - 0.08.
[0029] Hereinafter, as an example, a method for manufacturing an MCC containing Ni and element M will be described. First, a powder X containing Ni and element M is prepared. The powder X can be manufactured by a batch coprecipitation method or a continuous coprecipitation method.
[0030] Specifically, a nickel salt solution, a metal salt solution of element M, and a complexing agent are reacted by the continuous coprecipitation method described in JP-A-2002-201028 to produce a powder containing the metal composite hydroxide represented by the formula (A'). For example, a nickel salt solution, a cobalt salt solution, an aluminum salt solution, and a complexing agent are reacted to produce Ni (1-x) Al a Co b (OH) 2 A powder containing a metal composite hydroxide represented by (a+b=x) is produced.
[0031] The nickel salt that is the solute of the nickel salt solution is not particularly limited, but for example, at least one of nickel sulfate, nickel nitrate, nickel chloride, and nickel acetate can be used.
[0032] As the aluminum salt which is the solute of the aluminum salt solution, for example, at least one of aluminum sulfate and sodium aluminate can be used.
[0033] As the cobalt salt which is the solute of the cobalt salt solution, for example, at least one of cobalt sulfate, cobalt nitrate, cobalt chloride, and cobalt acetate can be used.
[0034] The metal salt solutions are used in a ratio corresponding to the composition ratio of the above formula (A). That is, the amount of each metal salt solution is specified so that the molar ratio of Ni and element M in the mixed solution containing the above metal salts corresponds to (1-x):x. Water is used as the solvent.
[0035] The complexing agent is capable of forming a complex with nickel ions and ions of element M (e.g., aluminum ions, cobalt ions) in an aqueous solution, and examples thereof include ammonium ion donors (ammonium hydroxide, ammonium sulfate, ammonium chloride, ammonium carbonate, ammonium fluoride, etc.), hydrazine, ethylenediaminetetraacetic acid, nitrilotriacetic acid, uracil diacetic acid, and glycine.
[0036] A complexing agent may or may not be used. When a complexing agent is used, the amount of the complexing agent contained in the mixed solution containing the nickel salt solution, the metal salt solution of element M, and the complexing agent is, for example, a molar ratio of the complexing agent to the total number of moles of the metal salts (nickel salt, metal salt of element M) that is greater than 0 and less than or equal to 2.0.
[0037] In the coprecipitation method, it is preferable to neutralize a solution containing at least a nickel salt solution, in this example, a mixed solution containing a nickel salt solution, a metal salt solution of element M, and a complexing agent under conditions of pH 10-13 and 20-80° C. Specifically, the temperature of the reaction vessel is set to 20-80° C., and an alkali metal hydroxide is added to the mixed solution so that the pH becomes 10-13. The alkali metal hydroxide is, for example, sodium hydroxide or potassium hydroxide.
[0038] In this specification, the pH value is defined as the value measured when the temperature of the mixed liquid is 40° C. If the temperature of the mixed liquid sampled from the reaction tank is not 40° C., the mixed liquid is heated or cooled to 40° C. before measuring the pH.
[0039] When the nickel salt solution, the metal salt solution of element M, and a complexing agent are continuously supplied to the reaction vessel, Ni and element M react with each other to produce a metal composite hydroxide represented by formula (A').
[0040] During the reaction, the temperature of the reaction vessel is controlled preferably within the range of 30-80°C, more preferably 50-80°C.
[0041] During the reaction, the pH value of the mixture in the reaction tank is set within the range of preferably 10-12, more preferably 10.5-12.0, and even more preferably 10.5-11.7, and the pH fluctuation is controlled within ±0.2.
[0042] The reaction vessel used in the continuous coprecipitation method may be an overflow type reaction vessel for separating the formed reaction precipitate.
[0043] When a metal composite hydroxide is produced by a batch coprecipitation method, examples of the reaction tank include a reaction tank that is not equipped with an overflow pipe, and an apparatus that has a mechanism for concentrating the overflowed reaction precipitate in a concentration tank connected to an overflow pipe and circulating it back to the reaction tank.
[0044] Various gases may be supplied into the reaction vessel, for example, inert gases such as nitrogen, argon or carbon dioxide, oxidizing gases such as air or oxygen, or a mixture thereof.
[0045] The average particle size of the second primary particles and secondary particles in the MCC can be controlled by appropriately controlling the concentration of the metal salt supplied to the reaction tank, the temperature of the reaction tank, the pH of the mixed solution in the reaction tank, etc. In addition, by using the MCC obtained by neutralization under the above-mentioned conditions, the initial efficiency of the lithium secondary battery can be improved.
[0046] After the above reaction, the neutralized reaction precipitate is washed. The reaction precipitate is preferably washed with water or an alkaline washing solution. As the alkaline washing solution, an aqueous sodium hydroxide solution is preferable. Also, washing may be performed using a washing solution containing elemental sulfur. As an example of a washing solution containing elemental sulfur, an aqueous solution of potassium or sodium sulfate can be given. This results in a wet cake containing a metal composite hydroxide and water.
[0047] After producing the wet cake, it is preferable to remove moisture from the wet cake before the step X so that the ratio of moisture contained in the wet cake is 5-25% by mass relative to the total mass of the wet cake. Examples of a method for removing moisture include centrifugation and suction filtration. The ratio of moisture contained in the wet cake immediately before the step X is preferably 5-23% by mass, more preferably 5-21% by mass relative to the total mass of the wet cake. If the ratio of moisture contained in the wet cake is 5% by mass or more relative to the total mass of the wet cake, the wet cake will be in a moderately moist state in the next step X, and the wet cake will flow, so that the surface of the metal composite hydroxide contained in the wet cake will be easily scraped. If the ratio of moisture contained in the wet cake is 25% by mass or less relative to the total mass of the wet cake, the surface of the metal composite hydroxide will be easily scraped in the next step X, and moisture can be sufficiently removed. As a result, it is possible to obtain MCC in which the average particle size of the first primary particles, the average particle size of the second primary particles, the ratio (A / B) of the average particle size A of the second primary particles to the average particle size B of the first primary particles, and the ratio of moisture are in the ranges described below. Furthermore, the initial efficiency of a lithium secondary battery using the obtained MCC can be improved.
[0048] In step X, the wet cake is heated while being fluidized, and the surface of the metal composite hydroxide is scraped. By heating, the moisture in the wet cake is removed. Step X is carried out in a heating device such as a fluidized drying device. Examples of the fluidized drying device include a rotary kiln and a paddle dryer.
[0049] Specifically, the wet cake is fed into the heating device through an inlet, and the moisture is removed while the wet cake is fluidized. The powder X that has passed through the heating device is discharged from the heating device through an outlet.
[0050] The maximum holding temperature in step X is preferably 100° C. or higher, and more preferably 120° C. or higher. The maximum holding temperature is preferably 300° C. or lower, and more preferably 250° C. or lower. The maximum holding temperature is preferably 100-300° C., and more preferably 120-250° C. When the maximum holding temperature is equal to or higher than the lower limit, moisture can be appropriately removed, and when the maximum holding temperature is equal to or lower than the upper limit, the crystal state of the metal composite hydroxide is unlikely to change.
[0051] The residence time of the wet cake in the heating device in step X is preferably 0.2 hours or more, and more preferably 0.5 hours or more. The residence time is preferably 8 hours or less, and more preferably 6 hours or less. The residence time is preferably 0.2 to 8 hours, and more preferably 0.5 to 6 hours. When the residence time is within the above range, the surface of the metal composite hydroxide is appropriately scraped.
[0052] In step X, the proportion of moisture contained in the wet cake immediately before step X relative to the residence time of the wet cake in the heating device is preferably 10.5 mass% / hour or less, more preferably 10.0 mass% / hour or less, preferably 0.50 mass% / hour or more, and more preferably 0.80 mass% / hour or more. The proportion of moisture contained in the wet cake immediately before step X relative to the residence time of the wet cake in the heating device is preferably 0.50-10.5 mass% / hour, more preferably 0.80-10.0 mass% / hour.
[0053] The wall friction distance of the wet cake in the heating device is preferably 300 to 5000 m. When the wall friction distance is 300 to 5000 m, the surface of the metal composite hydroxide is appropriately scraped. The wall friction distance is calculated by the following method.
[0054] When the wet cake moves due to the movement of the container itself in which the wet cake of the heating device resides, the movement is calculated using the following formula (1). Wall friction distance (m) = circumferential length of axial cross section of vessel (m) × vessel peripheral speed (rpm) × residence time (min) Formula (1) When the container of the heating device does not move and the wet cake moves due to the rotation of a rotor inside the container, the calculation is made using the following formula (2). Wall friction distance (m) = Circumference of the rotor orbit (m) × Circumferential speed of the rotor (rpm) × Residence time (min) Equation (2)
[0055] The atmosphere in step X may be air, oxygen, nitrogen, argon or a mixed gas of these, with air being preferred.
[0056] By heating the wet cake while fluidizing it under the above conditions, friction occurs between the particles of the metal composite hydroxide contained in the wet cake and between the particles and the moving surfaces of the wall surface, rotary blades, etc. of the fluidized drying device. Then, the surface of the metal composite hydroxide is scraped and becomes smooth. As a result, it is possible to obtain an MCC in which the average particle size of the first primary particles, the average particle size of the second primary particles, A / B, and the water content are within the ranges described below. Then, it is possible to improve the initial efficiency of a lithium secondary battery using the obtained MCC.
[0057] The moisture content of the powder X immediately after the step X is 1% by mass or less, preferably 0.9% by mass or less, and more preferably 0.85% by mass or less, based on the total mass of the powder X. When the moisture content of the powder X is 1% by mass or less, the initial efficiency of the lithium secondary battery obtained using the MCC is good. The lower limit of the moisture content is not particularly limited, but is, for example, 0.01% by mass. The moisture content of the powder X is preferably 0.01-1% by mass, more preferably 0.01-0.9% by mass, and even more preferably 0.01-0.85% by mass. By carrying out step X so that the moisture content of powder X immediately after step X falls within the above range, it is possible to obtain an MCC in which the average particle size of the first primary particles, the average particle size of the second primary particles, A / B, and the moisture content fall within the ranges described below.
[0058] (Moisture content) Here, the moisture content of the wet cake, powder X, and MCC described below can be calculated from the weight loss in a heat drying method using an infrared moisture meter, for example, according to the following formula (3): The amount of the sample to be measured in the following formula (3) is the amount of the wet cake, powder X, or MCC. Moisture content (mass%) = weight loss (g) / measured sample weight (g) × 100 Equation (3)
[0059] When MCC is powder X, the powder X after step X is MCC in one embodiment of the present invention. The MCC in one embodiment of the present invention may be sieved after step X.
[0060] In one embodiment of the present invention, when the MCC is a metal composite oxide powder, the powder X is heated to produce a metal composite oxide powder. If necessary, multiple heating steps may be performed. In this specification, the heating temperature refers to the temperature set in the device. In the case of multiple heating steps, the heating temperature refers to the temperature of the step in which heating is performed at the highest temperature among the steps.
[0061] The heating temperature is preferably 400 to 700° C., more preferably 450 to 680° C. When the heating temperature is within the above range, the metal composite hydroxide is sufficiently oxidized.
[0062] The time for holding the heating temperature is 0.1 to 20 hours, preferably 0.5 to 10 hours. The rate of temperature rise to the heating temperature is, for example, 50 to 400° C. / hour. The heating atmosphere can be air, oxygen, nitrogen, argon, or a mixture of these gases.
[0063] The inside of the device may be an atmosphere containing a suitable amount of oxygen. The oxygen-containing atmosphere may be a mixed gas atmosphere of an inert gas and oxygen, or may be an inert gas atmosphere in the presence of an oxidizing agent. By having the inside of the device be an atmosphere containing a suitable amount of oxygen, the transition metal contained in the metal composite hydroxide is oxidized to a suitable degree, making it easier to control the form of the metal composite oxide.
[0064] The oxygen or oxidizing agent in the oxygen-containing atmosphere should be sufficient to contain sufficient oxygen atoms to oxidize the transition metal.
[0065] When the oxygen-containing atmosphere is a mixed gas atmosphere of an inert gas and oxygen, the atmosphere inside the apparatus can be controlled by, for example, passing oxygen through the heating apparatus or bubbling oxygen into the mixed liquid.
[0066] As the oxidizing agent, peroxides such as hydrogen peroxide, peroxide salts such as permanganate, perchlorates, hypochlorites, nitric acid, halogens, ozone, or the like can be used.
[0067] When producing a metal composite oxide powder as MCC, by heating the powder X under the above-mentioned conditions, it is possible to obtain MCC in which the average particle size of the first primary particles, the average particle size of the second primary particles, A / B, and the moisture ratio described below are within the ranges described below.
[0068] The CAM produced by using the MCC produced by the above method can achieve a lithium secondary battery with high initial efficiency.
[0069] <Metal composite compounds> The MCC includes secondary particles which are aggregates of a plurality of first primary particles and a plurality of second primary particles, and includes at least Ni, wherein, when the dimension from the outermost surface of the secondary particle to the center of gravity in a cross section of the secondary particle is taken as 100%, the first primary particles are located in an area less than 10% from the outermost surface of the secondary particle, and the second primary particles are located in an area 90% or less from the center of gravity, and the ratio of the average particle diameter of the second primary particles to the average particle diameter of the first primary particles is 1.5 or more.
[0070] The MCC is composed of a plurality of particles. In other words, the MCC in this embodiment is in a powder form. In this embodiment, the MCC may contain only secondary particles, or may be a mixture of primary particles and secondary particles that do not constitute secondary particles.
[0071] Here, the term "primary particle" refers to a particle that does not have grain boundaries in appearance and that constitutes a secondary particle. More specifically, the term "primary particle" refers to a particle that does not have clear grain boundaries on the particle surface when the particle is observed at a magnification of 5000 to 20000 times using a scanning electron microscope or the like.
[0072] The proportion of water contained in MCC is preferably 1% by mass or less, more preferably 0.9% by mass or less, and even more preferably 0.85% by mass or less, based on the total mass of MCC. When the proportion of water in MCC is 1% by mass or less, the initial efficiency of a lithium secondary battery obtained using MCC is good. The lower limit of the proportion of water is not particularly limited, but is, for example, 0.01% by mass. The proportion of water in MCC is preferably 0.01-1% by mass, more preferably 0.01-0.9% by mass, and even more preferably 0.01-0.85% by mass. The moisture content of MCC is measured within 30 minutes after the MCC is exposed to the atmosphere. For example, this can be measured within 30 minutes after the MCC is manufactured, or within 30 minutes after the manufactured MCC is taken out of the container and exposed to the atmosphere after being stored in a container without being exposed to the atmosphere.
[0073] 1 is a schematic cross-sectional view of a secondary particle of MCC in one aspect of this embodiment. The secondary particle 40 includes a first primary particle 41 and a second primary particle 42. The first primary particle 41 means a primary particle located in an area less than 10% from the outermost surface of the secondary particle 40, that is, in an area from the outermost surface of the secondary particle 40 to a dashed line 43 in FIG. 1, when the dimension from the outermost surface of the secondary particle 40 to the center of gravity C in the cross section of the secondary particle 40 is taken as 100%. The second primary particle 42 means a primary particle located in an area 90% or less from the center of gravity C, that is, in an area surrounded by the dashed line 43 in FIG. 1.
[0074] In the above MCC, the first primary particles 41 present on the surface of the secondary particles are scraped off. Therefore, the average particle diameter of the first primary particles 41 is smaller than the average particle diameter of the second primary particles 42 present inside the secondary particles 40. Specifically, the ratio (A / B) of the average particle diameter A of the second primary particles 42 to the average particle diameter B of the first primary particles 41 is 1.5 or more, preferably 1.55 or more, and more preferably 1.6 or more. When A / B is equal to or more than the lower limit, the surface of the secondary particles 40 is moderately scraped and the surface is smooth. The initial efficiency of a lithium secondary battery obtained by using such MCC is improved. The upper limit of A / B is 2.5. A / B is preferably 1.5 to 2.5, more preferably 1.55 to 2.5, and more preferably 1.6 to 2.5.
[0075] Fig. 2 is a scanning electron microscope (SEM) image of secondary particles of MCC in one aspect of this embodiment. Fig. 3 is an SEM image of MCC with A / B less than 1.5. The surface of the secondary particles of MCC in Fig. 2 is smoother than the surface of the secondary particles of MCC in Fig. 3.
[0076] (Average particle size of first and second primary particles) The average particle diameter of the first and second primary particles is measured by the following method. First, secondary particles of MCC are dispersed in a resin for fixing particles. Then, the product is vacuum degassed, and the product obtained is sandwiched between aluminum plates and cured. This results in a cured resin containing secondary particles. The cured product is fixed to a sample stage and set in a cross-section sample preparation device (also called a cross-section polisher, for example, IB-19520CCP, manufactured by JEOL). The cross-section of the secondary particle is prepared by argon ion beam processing at an ion acceleration voltage of 6.0 kV. The cross-section of the obtained secondary particle is observed with a scanning electron microscope image (hereinafter, SEM, for example, product number: JSM-IT500HR, manufactured by JEOL), and a cross-sectional image is obtained. From the cross-sectional image, 10 secondary particles having a longest dimension within ±2 μm of the average particle diameter of the secondary particles described later are selected.
[0077] The center of gravity of the cross-sectional image is automatically determined using, for example, the Centroid function of the image analysis software ImageJ. The dimension from the outermost surface of the secondary particle to the center of gravity in the cross-sectional image of the secondary particle is taken as 100%, and 10 primary particles located in an area less than 10% from the outermost surface of the secondary particle are selected. The longest diameter of each primary particle is measured, and the arithmetic average value of the 10 primary particles is obtained. This operation is similarly performed for the 10 secondary particles selected when the cross-sectional image was obtained, and the arithmetic average value is taken as the average particle diameter B of the first primary particles.
[0078] The center of gravity of the cross-sectional image is determined as described above, and the dimension from the outermost surface of the secondary particle to the center of gravity in the cross-sectional image of the secondary particle is taken as 100%. Ten primary particles that are contained within an area of 90% or less from the center of gravity are selected. The longest diameter of each primary particle is measured, and the arithmetic average value of the 10 primary particles is obtained. This operation is performed for the 10 secondary particles selected when the cross-sectional image was obtained, and the arithmetic average value is taken as the average particle diameter A of the second primary particles.
[0079] B is preferably 0.1 μm or more, more preferably 0.2 μm or more, and even more preferably 0.3 μm or more. B is preferably 1.0 μm or less, more preferably 0.9 μm or less, and even more preferably 0.8 μm or less. B is preferably 0.1-1.0 μm, more preferably 0.2-0.9 μm, and even more preferably 0.3-0.8 μm. When B is in the above range, it can be said that the surface of the secondary particles is scraped and the surface is smooth. When MCC with B in the above range is used, the initial efficiency of the lithium secondary battery can be further improved.
[0080] A is preferably 0.2 μm or more, more preferably 0.3 μm or more, and even more preferably 0.4 μm or more. A is preferably 1.5 μm or less, more preferably 1.3 μm or less, and even more preferably 1.2 μm or less. A is preferably 0.2-1.5 μm, more preferably 0.3-1.3 μm, and even more preferably 0.4-1.2 μm. When A is in the above range, it can be said to be a highly crystalline MCC. When an MCC having A in the above range is used, the initial efficiency of a lithium secondary battery can be further improved.
[0081] The average particle size of the secondary particles is D 50 is preferably 5 μm or more, and more preferably 7 μm or more. 50 is preferably 20 μm or less, and more preferably 18 μm or less. 50 is preferably 5-20 μm, more preferably 7-18 μm. 50 By using MCC having a molecular weight of 1000 or less in the above range, the initial efficiency of the lithium secondary battery can be further improved.
[0082] MCC contains at least Ni, and preferably contains Ni and the element M. MCC may be any of the powder X containing at least Ni, a metal composite oxide powder, and a mixture thereof, but powder X containing at least Ni is preferred. MCC does not substantially contain Li.
[0083] The secondary particles contained in MCC contain Ni and the element M in a molar ratio represented by the above formula (A), and are preferably represented by the following formula (A''). The preferred range of x in formula (A'') is the same as the preferred range of x in the above formula (A). Ni (1-x) M x O α (OH) 2-β (A'') (In formula (A''), M is the element M, and formula (A'') satisfies 0 < x ≤ 0.5, 0 ≤ α ≤ 3, -0.5 ≤ β ≤ 2, and β - α < 2.)
[0084] The secondary particles contained in the MCC preferably contain Ni, element M1, and element M2 in the molar ratio represented by the formula (B) and are represented by the following formula (B''). The preferred ranges of y and z in formula (B'') are the same as the preferred ranges of y and z in formula (B). Ni (1-y-z) M1 y M2 z O α (OH) 2-β (B'')[[]END] (In formula (B''), M1 is one or more elements selected from the group consisting of Co, Mn, and Al, M2 is one or more elements selected from the group consisting of Fe, Cu, Ti, Mg, W, Mo, Nb, Zn, Sn, Zr, Ga, V, B, Si, S, and P, and formula (B'') satisfies 0 < y ≤ 0.5, 0 ≤ z ≤ 0.1, 0 < y + z ≤ 0.5, 0 ≤ α ≤ 3, -0.5 ≤ β ≤ 2, and β - α < 2.)
[0085] From the viewpoint of obtaining a lithium secondary battery with a high cycle retention rate, element M is preferably one or more elements selected from the group consisting of Mn, Co, Al, Ti, Mg, W, B, Nb, and Zr.
[0086] <Method for manufacturing CAM> The method for manufacturing CAM will be described. The method for manufacturing CAM at least includes firing a mixture of the MCC obtained in the aforementioned <Manufacture of MCC> and a lithium compound.
[0087] (1) Mixing of MCC and lithium compound This step is a step of mixing a lithium compound and MCC to obtain a mixture.
[0088] The lithium compound may be at least one of lithium carbonate, lithium nitrate, lithium acetate, lithium hydroxide, lithium oxide, lithium chloride, and lithium fluoride. Of these, lithium hydroxide and lithium carbonate or a mixture thereof are preferred.
[0089] The lithium compound and MCC are mixed in consideration of the composition ratio of the final target product to obtain a mixture. The amount (molar ratio) of Li relative to the total amount of metal atoms contained in MCC is preferably 1.00 or more, more preferably 1.02 or more. The mixture of the lithium compound and MCC is fired as described later to obtain a fired product.
[0090] (2) Firing the mixture CAM can be obtained by firing a mixture of MCC and a lithium compound. The firing may have multiple firing stages with different firing temperatures. For example, a first firing stage and a second firing stage in which firing is performed at a higher temperature than the first firing stage may be performed independently. Furthermore, firing stages with different firing temperatures and firing times may be performed. Before the main firing, a preliminary firing may be performed at a temperature lower than the main firing. In addition, after the main firing, a post-firing may be performed at a temperature lower than the main firing.
[0091] In this specification, the firing temperature means the temperature of the atmosphere in the firing furnace, and is the maximum temperature held during the firing process (hereinafter, sometimes referred to as the maximum holding temperature). In the case of a firing process having a plurality of firing stages, the firing temperature means the temperature of the stage in which firing is performed at the highest temperature among the firing stages. The above upper and lower limit values of the firing temperature can be combined arbitrarily.
[0092] The firing temperature is 500° C. or higher, and preferably 500-1100° C. If the firing temperature is 500° C. or higher, a CAM having a strong crystal structure can be obtained. Also, if the firing temperature is 1100° C. or lower, the volatilization of lithium ions on the particle surface can be reduced.
[0093] The retention time in the firing is preferably 1 to 50 hours. When the retention time in the firing is 1 hour or more, the reaction between the MCC and the lithium compound can be sufficiently enhanced. When the retention time in the firing is 50 hours or less, the volatilization of lithium ions is unlikely to occur, and the battery performance is improved.
[0094] For the firing, dry air, an oxygen atmosphere, an inert atmosphere, or the like is used depending on the desired composition. In this embodiment, firing in an oxygen atmosphere is preferred.
[0095] The mixture of MCC and a lithium compound may be sintered in the presence of an inert flux. The inert flux may remain in the sintered product, or may be removed by washing with a washing solution after sintering as described later. As the inert flux, for example, those described in WO2019 / 177032A1 can be used.
[0096] Examples of the firing furnace include a tunnel furnace, a roller hearth kiln, and a rotary kiln.
[0097] As described above, CAM can be obtained by firing the mixture of MCC and the lithium compound.
[0098] <cam> The CAM of this embodiment is obtained by the <manufacturing method of CAM> using the aforementioned MCC as a raw material. When the CAM is used, a lithium secondary battery with improved initial efficiency can be easily obtained.
[0099] <Lithium secondary battery> The configuration of a preferred lithium secondary battery when using the CAM will be described. Also, a positive electrode for a lithium secondary battery (hereinafter sometimes referred to as a positive electrode) suitable when using the CAM will be described.
[0100] An example of a preferred lithium secondary battery when using the CAM has a positive electrode, a negative electrode, a separator sandwiched between the positive electrode and the negative electrode, and an electrolytic solution disposed between the positive electrode and the negative electrode.
[0101] FIG. 4 is a schematic diagram showing an example of a lithium secondary battery. For example, a cylindrical lithium secondary battery 10 is manufactured as follows.
[0102] First, as shown in the partial enlarged view of FIG. 4, a pair of strip-shaped separators 1, a strip-shaped positive electrode 2 having a positive electrode lead 21 at one end, and a strip-shaped negative electrode 3 having a negative electrode lead 31 at one end are laminated in the order of separator 1, positive electrode 2, separator 1, negative electrode 3 and wound to form an electrode group 4.
[0103] The positive electrode 2 has, as an example, a positive electrode active material layer 2a containing CAM and a positive electrode current collector 2b on which the positive electrode active material layer 2a is formed on one side. Such a positive electrode 2 can be manufactured by first preparing a positive electrode mixture containing CAM, a conductive material, and a binder, and supporting the positive electrode mixture on one side of the positive electrode current collector 2b to form the positive electrode active material layer 2a.
[0104] The negative electrode 3 can include, as an example, an electrode in which a negative electrode mixture containing a negative electrode active material (not shown) is supported on a negative electrode current collector, and an electrode composed of only the negative electrode active material, and can be manufactured in the same manner as the positive electrode 2.
[0105] Next, the electrode group 4 and an insulator (not shown) are housed in the battery can 5, the bottom of the can is sealed, the electrode group 4 is impregnated with an electrolyte solution 6, and the electrolyte is disposed between the positive electrode 2 and the negative electrode 3. Furthermore, the upper part of the battery can 5 is sealed with a top insulator 7 and a sealing body 8, whereby a lithium secondary battery 10 can be manufactured.
[0106] The shape of the electrode group 4 can be, for example, a columnar shape such that the cross-sectional shape when the electrode group 4 is cut perpendicular to the winding axis is a circle, an ellipse, a rectangle, or a rectangle with rounded corners.
[0107] The shape of a lithium secondary battery having such an electrode group 4 can be any shape defined by IEC60086, which is a standard for batteries defined by the International Electrotechnical Commission (IEC), or JIS C 8500. For example, cylindrical or rectangular shapes can be used.
[0108] Furthermore, the lithium secondary battery is not limited to the above-mentioned wound type configuration, and may be a laminated type configuration in which a laminated structure of a positive electrode, a separator, a negative electrode, and a separator is repeatedly stacked. Examples of the laminated type lithium secondary battery include a so-called coin type battery, a button type battery, and a paper type (or sheet type) battery.
[0109] For the positive electrode, separator, negative electrode, and electrolyte constituting the lithium secondary battery, for example, the configurations, materials, and manufacturing methods described in
[0113] to
[0140] of WO2022 / 113904A1 can be used.
[0110] <All-solid-state lithium secondary battery> Next, a positive electrode using the CAM according to one embodiment of the present invention and an all-solid-state lithium secondary battery including this positive electrode will be described while explaining the configuration of the all-solid-state lithium secondary battery.
[0111] FIG. 5 is a schematic diagram showing an example of the all-solid-state lithium secondary battery of this embodiment. The all-solid-state lithium secondary battery 1000 shown in FIG. 5 has a laminate 100 having a positive electrode 110, a negative electrode 120, and a solid electrolyte layer 130, and an exterior body 200 that houses the laminate 100. The all-solid-state lithium secondary battery 1000 may also have a bipolar structure in which a positive electrode active material and a negative electrode active material are arranged on both sides of a current collector. A specific example of the bipolar structure is the structure described in JP-A-2004-95400. The materials constituting each member will be described later.
[0112] The positive electrode 110 has a positive electrode active material layer 111 and a positive electrode current collector 112. The positive electrode active material layer 111 contains the above-mentioned CAM and a solid electrolyte. The positive electrode active material layer 111 may also contain a conductive material and a binder.
[0113] The negative electrode 120 has a negative electrode active material layer 121 and a negative electrode current collector 122. The negative electrode active material layer 121 contains a negative electrode active material. The negative electrode active material layer 121 may also contain a solid electrolyte and a conductive material.
[0114] The laminate 100 may have an external terminal 113 connected to the positive electrode current collector 112 and an external terminal 123 connected to the negative electrode current collector 122. In addition, the all-solid-state lithium secondary battery 1000 may have a separator between the positive electrode 110 and the negative electrode 120.
[0115] The all-solid-state lithium secondary battery 1000 further includes an insulator (not shown) that insulates the laminate 100 from the exterior body 200 , and a sealing body (not shown) that seals the opening 200 a of the exterior body 200 .
[0116] A container molded from a highly corrosion-resistant metal material such as aluminum, stainless steel, or nickel-plated steel can be used as the exterior body 200. Also, a container formed into a bag shape from a laminate film having at least one surface treated to be corrosion-resistant can be used as the exterior body 200.
[0117] Examples of the shape of the all-solid-state lithium secondary battery 1000 include a coin type, a button type, a paper type (or a sheet type), a cylindrical type, a square type, and a laminate type (pouch type).
[0118] The all-solid-state lithium secondary battery 1000 is illustrated as having one laminate 100 as an example, but the present embodiment is not limited to this. The all-solid-state lithium secondary battery 1000 may have a configuration in which the laminate 100 is used as a unit cell, and a plurality of unit cells (laminated bodies 100) are sealed inside an exterior body 200.
[0119] For the all-solid-state lithium secondary battery, for example, the configuration, materials, and manufacturing method described in
[0151] to
[0181] of WO2022 / 113904A1 can be used.
[0120] The positive electrode having the above-mentioned configuration has the above-mentioned CAM, and therefore can provide a lithium secondary battery with high initial efficiency.
[0121] Furthermore, the lithium secondary battery having the above-mentioned configuration has a high initial efficiency since it has the above-mentioned positive electrode.
[0122] In another aspect, the present invention includes the following embodiments.
[14] A method for producing MCC powder, comprising a step X of heating a wet cake containing a metal composite hydroxide containing at least Ni and moisture while flowing it in a heating device, and scraping a surface of the metal composite hydroxide contained in the wet cake, wherein a ratio of the moisture contained in the wet cake immediately before the step X is 5-21 mass% with respect to a total mass of the wet cake, and in the step X, a ratio of the moisture contained in the wet cake immediately before the step X with respect to a residence time of the wet cake in the heating device is 10.0 mass% / hour or less.
[15] The method for producing an MCC powder according to
[14] , wherein the maximum holding temperature in step X is 120-250°C.
[16] The method for producing an MCC powder according to
[14] or
[15] , wherein the residence time is 0.5-6 hours.
[17] The method for producing an MCC powder according to any one of
[14] to
[16] , wherein the proportion of moisture contained in the powder X immediately after the step X is 1 mass% or less relative to the total mass of the powder X.
[18] The method for producing an MCC powder according to any one of
[14] to
[17] , further comprising a step of neutralizing a solution containing at least a nickel salt solution under conditions of pH 10.5-11.7 and 50-80° C. prior to the step X.
[19] The method for producing an MCC powder according to any one of
[14] to
[18] , further comprising, prior to the step X, a step of removing moisture from the wet cake such that the proportion of moisture contained in the wet cake is 5 to 21 mass% relative to the total mass of the wet cake.
[20] The method for producing an MCC powder according to any one of
[14] to
[19] , wherein the metal composite hydroxide further contains the element M.
[21] An MCC powder comprising secondary particles which are aggregates of a plurality of first primary particles and a plurality of second primary particles, and moisture, and which contains at least Ni, wherein the A / B is 1.6 to 2.5.
[22] The MCC powder according to
[21] , wherein B is 0.3-0.8 μm.
[23] The MCC powder according to
[21] or
[22] , wherein the proportion of moisture contained in the MCC powder is 0.01-0.85 mass% based on the total mass of the MCC powder.
[24] D above 50 The MCC powder according to any one of
[21] to
[23] , wherein the particle size is 7-18 μm.
[25] The MCC powder according to any one of
[21] to
[24] , further containing the element M.
[26] A method for producing CAM, comprising calcining a mixture of the MCC powder according to any one of
[21] to
[25] and a lithium compound. EXAMPLES
[0123] The present invention will be described in detail below with reference to examples, but the present invention is not limited to the following description.
[0124] <Composition analysis> The composition analysis of MCC (metal complex hydroxide) produced by the method described below was carried out by the method described above in "Composition analysis of MCC".
[0125] <Average particle size of first and second primary particles> The average particle size B of the first primary particles and the average particle size A of the second primary particles of the MCC produced by the method described below were measured by the method described above in "Average particle sizes of the first and second primary particles."
[0126] <Cumulative volumetric particle size> The average particle size of the secondary particles of the MCC produced by the method described below was measured by the above-mentioned "cumulative volumetric particle size" method.
[0127] <Moisture content> The moisture content of the wet cake and the powder containing the metal composite hydroxide (MCC) was measured by the method described above in (Moisture content).
[0128] <Preparation of positive electrodes for lithium secondary batteries> A positive electrode for a lithium secondary battery was produced by the method described above in the "Method of producing a positive electrode for a lithium secondary battery" using the CAM obtained by the production method described later.
[0129] <Preparation of lithium secondary battery> Using the positive electrode for lithium secondary battery prepared by the above method, a lithium secondary battery was prepared by the method described in the above "Method of preparing lithium secondary battery".
[0130] <First-run efficiency> For the lithium secondary battery produced by the above method, the initial efficiency was measured by the method described in the above-mentioned method for measuring "initial efficiency".
[0131] Example 1 Water was placed in a reaction vessel equipped with a stirrer and an overflow pipe, and then an aqueous sodium hydroxide solution was added and the liquid temperature was maintained at 70°C.
[0132] A mixed solution was prepared by mixing an aqueous solution of nickel sulfate, an aqueous solution of cobalt sulfate, and an aqueous solution of aluminum sulfate such that the molar ratio of Ni, Co, and Al was 0.88:0.09:0.03.
[0133] Next, in the reaction vessel, an aqueous solution of ammonium sulfate was continuously added as a complexing agent to the mixed solution while stirring. An aqueous solution of sodium hydroxide was added dropwise at appropriate times so that the pH of the mixed solution in the reaction vessel became 11.6 (measurement temperature: 40°C), and reaction precipitate 1 was obtained.
[0134] The reaction precipitate 1 was washed with pure water to obtain a wet cake 1, and then dehydrated by suction filtration so that the ratio of water contained in the wet cake 1 to the total mass of the wet cake 1 was 19.2 mass%. The wet cake 1 was charged into a rotary kiln (product name, manufactured by Shimakawa Seisakusho Co., Ltd., the circumference of the container of the firing furnace was 1.5 m), and the wet cake 1 was heated at 140°C with a peripheral speed of 2 rpm and a residence time of 5 hours while being fluidized, and a powder containing the metal composite hydroxide 1 was obtained. At this time, the wall friction distance of the wet cake 1 in the rotary kiln was 900 m. When the composition of the metal composite hydroxide 1 was analyzed, it was found that in formula (A'), x = 0.12, and the element M was Co and Al. In formula (B'), y = 0.12, z = 0, and the element M1 was Co and Al.
[0135] The powder containing the metal composite hydroxide 1 was heated at 650° C. for 5 hours in an air atmosphere, and then cooled to room temperature to obtain the metal composite oxide powder 1.
[0136] Lithium hydroxide was weighed out so that the amount (molar ratio) of Li relative to the total amount 1 of Ni, Co, and Al contained in the metal composite oxide powder 1 was 1.05. Mixture 1 was obtained by mixing the metal composite oxide powder 1 and lithium hydroxide.
[0137] This mixture 1 was calcined at 750° C. for 5 hours in an oxygen atmosphere to obtain CAM-1.
[0138] Example 2 Water was placed in a reaction vessel equipped with a stirrer and an overflow pipe, and then an aqueous sodium hydroxide solution was added and the liquid temperature was maintained at 70°C.
[0139] A mixed solution was prepared by mixing an aqueous solution of nickel sulfate, an aqueous solution of manganese sulfate, and an aqueous solution of aluminum sulfate such that the molar ratio of Ni, Mn, and Al was 0.93:0.035:0.035.
[0140] Next, in the reaction vessel, an aqueous solution of ammonium sulfate was continuously added as a complexing agent to the mixed solution while stirring. An aqueous solution of sodium hydroxide was added dropwise at appropriate times so that the pH of the mixed solution in the reaction vessel became 11.4 (measurement temperature: 40°C), and a reaction precipitate 2 was obtained.
[0141] The reaction precipitate 2 was washed with pure water to obtain a wet cake 2, and then the wet cake 2 was dehydrated by suction filtration so that the ratio of water contained in the wet cake 2 to the total mass of the wet cake 2 was 18.7 mass%, and other than that, a powder containing a metal composite hydroxide 2 was obtained by the same operation as in Example 1. When a composition analysis was performed on the metal composite hydroxide 2, it was found that in the formula (A'), x = 0.07, and the element M was Mn and Al. In the formula (B'), y = 0.07, z = 0, and the element M1 was Mn and Al.
[0142] The powder containing the metal composite hydroxide 2 was heated at 650° C. for 5 hours in an air atmosphere, and then cooled to room temperature to obtain the metal composite oxide powder 2.
[0143] Lithium hydroxide was weighed out so that the amount (molar ratio) of Li relative to the total amount of Ni, Mn, and Al contained in the metal composite oxide powder 2, which was 1, was 1.02. Mixture 2 was obtained by mixing the metal composite oxide powder 2 and lithium hydroxide.
[0144] This mixture 2 was calcined at 750° C. for 5 hours in an oxygen atmosphere to obtain CAM-2.
[0145] Example 3 Water was placed in a reaction vessel equipped with a stirrer and an overflow pipe, and then an aqueous solution of sodium hydroxide was added and the liquid temperature was maintained at 50°C.
[0146] A mixed solution was prepared by mixing an aqueous solution of nickel sulfate, an aqueous solution of cobalt sulfate, and an aqueous solution of manganese sulfate such that the molar ratio of Ni, Co, and Mn was 0.83:0.12:0.05.
[0147] Next, in the reaction vessel, an aqueous solution of ammonium sulfate was continuously added as a complexing agent to the mixed solution while stirring. An aqueous solution of sodium hydroxide was added dropwise at appropriate times so that the pH of the mixed solution in the reaction vessel became 11.4 (measurement temperature: 40°C), and reaction precipitate 3 was obtained.
[0148] The reaction precipitate 3 was washed with pure water to obtain a wet cake 3, and then the wet cake 3 was dehydrated by suction filtration so that the ratio of water contained in the wet cake 3 to the total mass of the wet cake 3 was 5.0 mass %, and other operations were performed in the same manner as in Example 1 to obtain a powder containing a metal composite hydroxide 3. When a composition analysis was performed on the metal composite hydroxide 3, it was found that in formula (A'), x = 0.17, and the element M was Co and Mn. In formula (B'), y = 0.17, z = 0, and the element M1 was Co and Mn.
[0149] The powder containing the metal composite hydroxide 3 was heated at 650° C. for 5 hours in an air atmosphere, and then cooled to room temperature to obtain the metal composite oxide powder 3.
[0150] Lithium hydroxide was weighed out so that the amount (molar ratio) of Li relative to the total amount of Ni, Co, and Mn contained in the metal composite oxide powder 3, which was 1, was 1.10. Mixture 3 was obtained by mixing the metal composite oxide powder 3 and lithium hydroxide.
[0151] This mixture 3 was calcined at 650° C. for 5 hours in an oxygen atmosphere to obtain CAM-3.
[0152] Example 4 The wet cake 2 was dehydrated by suction filtration so that the ratio of the moisture contained in the wet cake 2 to the total mass of the wet cake 2 was 19.4 mass%. The wet cake 2 was charged into a rotary kiln (product name, manufactured by Shimakawa Manufacturing Co., Ltd., the perimeter length of the firing furnace container was 1.5 m), and the wet cake 2 was heated at 140 ° C. with a peripheral speed of 2 rpm and a residence time of 2 hours while being fluidized, and a powder containing a metal composite hydroxide 4 was obtained. At this time, the wall friction distance of the wet cake 2 in the rotary kiln was 360 m. When the composition of the metal composite hydroxide 4 was analyzed, x = 0.07 in formula (A'), and the element M was Co and Al. In formula (B'), y = 0.07, z = 0, and the element M1 was Mn and Al. Using the powder containing the metal composite hydroxide 4, the same operation as in Example 1 was performed to obtain CAM-4.
[0153] Comparative Example 1 The wet cake 1 was placed in a static calcination furnace (FC-2000, manufactured by AS ONE) and heated at 120°C for 24 hours to obtain a powder containing metal composite hydroxide C1. A composition analysis of the metal composite hydroxide C1 revealed that in formula (A'), x = 0.12, and the element M was Co and Al. In formula (B'), y = 0.12, z = 0, and the element M1 was Co and Al. Using the powder containing metal composite hydroxide C1, the same operations as in Example 1 were carried out to obtain CAM-C1.
[0154] Comparative Example 2 Water was placed in a reaction vessel equipped with a stirrer and an overflow pipe, and then an aqueous sodium hydroxide solution was added and the liquid temperature was maintained at 45°C.
[0155] A mixed solution was prepared by mixing an aqueous solution of nickel sulfate, an aqueous solution of manganese sulfate, and an aqueous solution of aluminum sulfate such that the molar ratio of Ni, Mn, and Al was 0.93:0.035:0.035.
[0156] Next, in the reaction vessel, an aqueous solution of ammonium sulfate was continuously added as a complexing agent to the mixed solution under stirring. An aqueous solution of sodium hydroxide was added dropwise at appropriate times so that the pH of the mixed solution in the reaction vessel became 12.5 (measurement temperature: 40°C), and reaction precipitate 4 was obtained. The reaction precipitate 4 was washed with pure water to obtain a wet cake 4, and then the wet cake 4 was dehydrated by suction filtration until the ratio of water contained in the wet cake 4 to the total mass of the wet cake 4 became 0.75 mass%, and other operations were performed in the same manner as in Example 1 to obtain a powder containing a metal composite hydroxide C2. When the composition of the metal composite hydroxide C2 was analyzed, it was found that in formula (A'), x = 0.07, and the element M was Mn and Al. In formula (B'), y = 0.07, z = 0, and the element M1 was Mn and Al. Using the powder containing the metal composite hydroxide C2, the same operations as in Example 1 were performed thereafter to obtain CAM-C2.
[0157] Comparative Example 3 The same operation as in Example 1 was performed, except that the wet cake 2 was dehydrated by suction filtration so that the ratio of the moisture contained in the wet cake 2 to the total mass of the wet cake 2 was 30.4 mass%, and a powder containing a metal composite hydroxide C3 was obtained. When the composition of the metal composite hydroxide C3 was analyzed, it was found that in formula (A), x = 0.07, and the element M was Mn and Al. In formula (B'), y = 0.07, z = 0, and the element M1 was Mn and Al. CAM-C3 was obtained using the powder containing the metal composite hydroxide C3, and the same operation as in Example 1 was performed thereafter. Note that, the average particle size of A, B, A / B, and secondary particles of the powder containing the metal composite hydroxide C3 was measured after putting it into a static calcination furnace (manufactured by AS ONE, FC-2000) and heating it at 120 ° C for 12 hours before observation with SEM, and the ratio of moisture to the total mass of the powder containing the metal composite hydroxide C3 was set to 0.56 mass%.
[0158] Comparative Example 4 The wet cake 2 was dehydrated by suction filtration so that the ratio of the moisture contained in the wet cake 2 to the total mass of the wet cake 2 was 16.5% by mass. The wet cake 2 was charged into a rotary kiln (product name, manufactured by Shimakawa Manufacturing Co., Ltd., the perimeter length of the firing furnace container was 1.5 m), and the wet cake 2 was heated at 140°C with a peripheral speed of 2 rpm and a residence time of 1 hour while being fluidized, to obtain a powder containing the metal composite hydroxide C4. At this time, the wall friction distance of the wet cake 2 in the rotary kiln was 180 m. When the composition of the metal composite hydroxide C4 was analyzed, it was found that in formula (A'), x = 0.07, and the element M was Mn and Al. In formula (B'), y = 0.07, z = 0, and the element M1 was Mn and Al. Using the powder containing the metal composite hydroxide C4, the same operation as in Example 1 was performed to obtain CAM-C4.
[0159] In Examples 1 to 4 and Comparative Examples 1 to 4, y and z in formula (B'), pH in the reaction tank (referred to as pH in Table 1), temperature in the reaction tank, heating method for the wet cake, moisture content of the wet cake and powder containing metal composite hydroxide (MCC), residence time of the wet cake in the rotary kiln or static calcination furnace (referred to as residence time in Table 1), moisture content of the wet cake / residence time, A, B, A / B, and D. 50 are shown in Table 1. Furthermore, the powders containing the metal composite hydroxides 1 to 4 of Examples 1 to 4 are designated MCC-1 to MCC-4, and the powders containing the metal composite hydroxides C1 to C4 of Comparative Examples 1 to 4 are designated MCC-C1 to MCC-C4. Table 1 also shows the initial efficiency of lithium secondary batteries produced using each MCC.
[0160] [Table 1]
[0161] A / B was 1.5 or more in MCC-1 to MCC-4 of Examples 1 to 4. Furthermore, the initial efficiency of the lithium secondary batteries using MCC-1 to MCC-4 was 83.0% or more.
[0162] On the other hand, in Comparative Example 1 in which the wet cake was heated in a static firing furnace, A / B of MCC-C1 was 1.11. In Comparative Example 2 in which the proportion of moisture contained in the wet cake was 0.75 mass% relative to the total mass of the wet cake, A / B of MCC-C2 was 1.25. In Comparative Example 3 in which the proportion of moisture contained in the wet cake was 30.4 mass% relative to the total mass of the wet cake, A / B of MCC-C3 was 1.13. In Comparative Example 4 in which the proportion of moisture contained in the wet cake / residence time was 16.50 mass% / h, A / B of MCC-C4 was 1.25. The initial efficiency of the lithium secondary batteries using MCC-C1 to MCC-C4 was less than 83.0%. [Industrial Applicability]
[0163] According to the present invention, there are provided an MCC capable of producing a lithium secondary battery with high initial efficiency, a method for producing an MCC, and a method for producing a CAM. [Explanation of symbols]
[0164] REFERENCE SIGNS LIST 1...separator, 2...positive electrode, 2a...positive electrode active material layer, 2b...positive electrode current collector, 3...negative electrode, 4...electrode group, 5...battery can, 6...electrolyte, 7...top insulator, 8...sealing body, 10...lithium secondary battery, 21...positive electrode lead, 31...negative electrode lead, 40...secondary particle, 41...first primary particle, 42...second primary particle, 100...laminated body, 110...positive electrode, 111...positive electrode active material layer, 112...positive electrode current collector, 113...external terminal, 120...negative electrode, 121...negative electrode active material layer, 122...negative electrode current collector, 123...external terminal, 130...solid electrolyte layer, 200...exterior body, 200a...opening, 1000...all-solid-state lithium secondary battery< / cam>
Claims
1. The method includes a step X of heating a wet cake containing at least a metal composite hydroxide containing Ni and moisture while flowing the wet cake in a heating device, and scraping a surface of the metal composite hydroxide contained in the wet cake, The proportion of the water contained in the wet cake immediately before the step X is 5% by mass or more and 25% by mass or less with respect to the total mass of the wet cake, a ratio of the moisture contained in the wet cake immediately before the step X to a residence time of the wet cake in the heating device is 11 mass % / hour or less.
2. The method for producing a metal composite compound powder according to claim 1, wherein the maximum holding temperature in the step X is 100°C or higher and 300°C or lower.
3. The method for producing a metal composite compound powder according to claim 1 or 2, wherein the residence time is 0.2 to 8 hours.
4. 3. The method for producing a metal composite compound powder according to claim 1, wherein a proportion of moisture contained in the powder containing the metal composite hydroxide immediately after the step X is 1 mass % or less with respect to a total mass of the powder containing the metal composite hydroxide.
5. The method for producing a metal composite compound powder according to claim 1 or 2, further comprising, prior to the step X, a step of neutralizing a solution containing at least a nickel salt solution under conditions of pH 10 to pH 13 and 20° C. to 80° C.
6. 3. The method for producing a metal composite compound powder according to claim 1 or 2, further comprising, before the step X, a step of removing moisture from the wet cake such that a proportion of moisture contained in the wet cake is 5 mass % or more and 25 mass % or less with respect to a total mass of the wet cake.
7. 3. The method for producing a metal composite compound powder according to claim 1 or 2, wherein the metal composite hydroxide further contains an element M, and the element M is one or more elements selected from the group consisting of Co, Mn, Al, Fe, Cu, Ti, Mg, W, Mo, Nb, Zn, Sn, Zr, Ga, V, B, Si, S and P.
8. A metal composite compound powder including secondary particles which are aggregates of a plurality of first primary particles and a plurality of second primary particles, and including at least Ni, when a dimension from an outermost surface of the secondary particle to a center of gravity in a cross section of the secondary particle is taken as 100%, the first primary particle is located in an area of less than 10% from the outermost surface of the secondary particle, the second primary particles are located in an area of 90% or less from the center of gravity, A metal composite compound powder, wherein a ratio of an average particle size of the second primary particles to an average particle size of the first primary particles is 1.5 or more.
9. The metal complex compound powder according to claim 8 , wherein the first primary particles have an average particle size of 0.1 μm or more and 1.0 μm or less.
10. The metal complex compound powder according to claim 8 or 9, wherein the secondary particles have an average particle size of 5 μm or more and 20 μm or less.
11. The metal composite compound powder according to claim 8 or 9, wherein a proportion of moisture contained in the metal composite compound powder is 1 mass % or less with respect to a total mass of the metal composite compound powder.
12. The metal composite compound powder according to claim 8 or 9, further comprising an element M, the element M being one or more elements selected from the group consisting of Co, Mn, Al, Fe, Cu, Ti, Mg, W, Mo, Nb, Zn, Sn, Zr, Ga, V, B, Si, S and P.
13. A method for producing a positive electrode active material for a lithium secondary battery, comprising firing a mixture of the metal complex compound powder according to claim 8 or 9 and a lithium compound.
Citation Information
Patent Citations
Process for manufacturing positive electrode active material for lithium secondary battery, and active material precursor powder to be used therein
WO2014061580A1